(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The purpose of the present study is to determine the psycho-physiological effects of mechanical properties of compression hosieries (CHs) with different pressure levels and longitudinal gradient distribution profiles on the wearing comfort perception and blood circulation performance of the lower extremities in vivo. The mechanical properties of CHs (tensile, shearing, and bending) significantly influencing pressure level performances have been instrumentally estimated. Blood circulation as the main physiological parameter was investigated along the long and short saphenous veins and popliteal veins (PopV) of a total of 24 lower extremities of twelve female subjects by using Colour Doppler Ultrasound equipment in conjunction with four-hour subjective wear trials in a controlled environmental chamber. The study demonstrated that the mechanical properties of CHs fabric produced gradient variations along hosiery hose and among pressure levels. The skin pressures applied by CHs with four pressure levels significantly decreased the cross-sectional areas, and increased the mean flow velocities (VP mean) of the PopV by 15.70%, 29.80%, 31.30 % and 24.20%, respectively. Wearing comfort and acceptance degree significantly correlated with mechanical quality of CHs textiles. Light and mild compression by CHs provides the subjects more comfort sensory perception for long-term wearing period. The application of CHs textiles appears to be effective in preventing venous dilation and improving blood circulation in the lower extremities when wearers lack of physical activities. The fabrics with lower elasticity and higher bending rigidity properties produced higher pressure; while no significant differences in increasing blood circulation was found among mild, moderate, and strong pressure levels. An illustrative plot represents the integrative relationships between multiple materials mechanical properties, pressure performance, and resultant physiological responses and subjective comfort sensory perception, which provide a reference for product designer and physician in development and application of functional compression hosiery textiles.